2005
DOI: 10.1080/09513590400027224
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index, body fat mass and the occurrence of amenorrhea in ballet dancers

Abstract: To evaluate the connection between menstrual disorders and body fat mass, we examined a group of 30 ballet dancers and a group of 30 non-athletic girls (controls). Body mass index (BMI) was calculated and percent body fat (FAT%) was measured using the bioelectrical impedance method. A questionnaire was used to obtain age at menarche and duration of menstrual cycles. Ballet dancers had significantly lower values of BMI (18.56 +/- 1.53 vs. 19.96 +/- 2.12 kg/m2) and FAT% (18.85 +/- 4.50 vs. 23.41 +/- 4.34%) compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 15 publications
4
32
0
6
Order By: Relevance
“…Similar findings were obtained for male and female ballet dancers from the Croatian National Theatre Ballet [27]. On the other hand, BMI values that were significantly lower than normal ones were noted by Serbian researchers who studied a group of 30 female ballet dancers: according to the classification of BMI levels, 50% of those ballet dancers were underweight [24]. Low BMI values were also found for female ballet dancers examined in the research performed by Dutch and Finnish researchers, who found significantly lower BMI values in dancers than in the control group (18.9 vs. 21.3, respectively) [32].…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…Similar findings were obtained for male and female ballet dancers from the Croatian National Theatre Ballet [27]. On the other hand, BMI values that were significantly lower than normal ones were noted by Serbian researchers who studied a group of 30 female ballet dancers: according to the classification of BMI levels, 50% of those ballet dancers were underweight [24]. Low BMI values were also found for female ballet dancers examined in the research performed by Dutch and Finnish researchers, who found significantly lower BMI values in dancers than in the control group (18.9 vs. 21.3, respectively) [32].…”
Section: Discussionsupporting
confidence: 64%
“…The results obtained for the Skerlj index were similar: based on the values of 31.8 (for girls aged 14-15 years) and 31.6 (for those aged 16-17 years), the subjects could be classified as thin. As far as the Pignet index is concerned, it amounted to 29.7 for younger girls and 31.3 for older 24,[192][193][194][195][196][197] ones, which means that the former had a weak physique and the latter had a very weak one. Body proportions were assessed by means of the chest to hip circumference ratio.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations